Unusual foreign body in oropharynx: a case report - Gupta, Richa; Agrawal, Vishnu; Gupta, Shikha; Gupta, Saurabh (International Journal of Research in Medical Sciences, 2017)
Foreign body in oropharynx is common occurrence. We report a case of a 7 month old male baby who presented with complaint of feeding difficulty and later diagnosed as case of foreign body oropharynx i.e. wheat stalk of 5 cm with overlying husk based on detailed history and meticulous examination.